M100S project: math MOOCs from Polytechnic of Porto – development, continuance, and use - Soares, Filomena Baptista (2018)
This chapter presents the M100S project, a math MOOC platform from the e-learning unit of the Polytechnic of Porto (P.PORTO). Reference is made to all motivational, structural, and fundamental steps of this process of creation and development, from its origin to the present day, and a brief analysis of the advantages and disadvantages of these recent educational resources. The general structure adopted for these mathematics MOOCs is presented, with all its features, and the difficulties inherent to the development of these courses from scratch are analyzed, both regarding the technological and financial support available as well as the human resources enrolled. Finally, several internal practices and applications made by means of the most varied open resources, specifically developed for these MOOCs and other existing ones from the MatActiva project, in Portuguese, both in a b-learning perspective and in the development of flipped teaching strategies, are mentioned.